Kenapa Seseorang Melakukan Manipulasi Laporan Keuangan?: Studi dengan Pendekatan Skenario Kasus Dilema Etika - Hafiez Sofyani; Nadia Rahma (Jurnal Akuntansi dan Keuangan Islam, 2017)
This study aims to identify the reasons why individu wants or does not to manipulates the financial statements. The design of this study refer to ethical dilemma scenarios developed by Sofyani and Pramita (2014). The samples are students of accounting from one university in Yogyakarta, which has joined in financial accounting and taxation courses. Data was analyzed using thematic deductive analysis approach (Braun and Clarke, 2006). The study find that the majority of students who want to manipulate the financial statements due to the reason that the manipulation did not force the legislation. While the majority of students who refuse the manipulation of financial statements reasoned that it violates religion obligation, because there is an element of falsehood. The results of this study can be used as the basis to develop further study with a broader scope, such as with survey approach